Membangun kekuatan kolektif perempuan desa: Pelatihan kepemimpinan dan advokasi untuk peningkatan partisipasi dalam musyawarah desa di Sukaharja, Bogor - Jaenal Mutakim; Srikoeswantono; Ahmad Tijari (IKIP SILIWANGI, 2025)
Women in Sukaharja Village, Sukamakmur District, Bogor Regency face serious challenges, including limited access to clean water, proper sanitation, and low involvement in village development decision-making. Although women make up nearly half of the population, their aspirations are often overlooked in village deliberations. To address this issue, this community service program aimed to strengthen women’s capacity and participation through leadership and advocacy training. The implementation method was participatory, consisting of needs assessment, curriculum development, interactive training sessions, and evaluation and monitoring. The training was conducted at the Sukaharja Village Hall involving 30 women from PKK, Village Consultative Body (BPD), posyandu cadres, women’s business groups, and local women leaders. The results showed that all participants completed the sessions, two women’s advocacy groups were established, and women’s participation in village deliberations increased significantly by up to 80%. In addition, the program produced outputs such as a digital training module and educational video, while also providing practical social engagement for students. In conclusion, leadership and advocacy training successfully enhanced both individual and collective capacity of village women as agents of change, thereby promoting more inclusive, gender-responsive, and sustainable village development.Keywords: Women’s empowerment, leadership, advocacy, village development, gender equality